A comparative overview of large-scale battery systems for electricity storage - Poullikkas, Andreas (2013)
In this work, an overview of the different types of batteries used for large-scale electricity storage is carried out. In particular, the current operational large-scale battery energy storage systems around the world with their applications are identified and a comparison between the different types of batteries, as well as with other types of large-scale energy storage systems, is presented. The analysis has shown that the largest battery energy storage systems use sodium-sulfur batteries, whereas the flow batteries and especially the vanadium redox flow batteries are used for smaller battery energy storage systems. The battery electricity storage systems are mainly used as ancillary services or for supporting the large scale solar and wind integration in the existing power system, by providing grid stabilization, frequency regulation and wind and solar energy smoothing.